State Hygiene School as a Department of Education in the National Institute of Hygiene in Warsaw - Kazimiera Ćwiek-Ludwicka (National Institute of Public Health - National Institute of Hygiene, 2019)
The article presents the history of the establishment of the State School of Hygiene (PSH) in Poland after the First World War. The difficulties faced by the public health service in a country destroyed by war and created after the reunification of the lands, which for over 150 years remained under the control of three powers, were pointed out. It discusses how the foundations of modern teaching in the field of public health were created in the National Institute of Hygiene (PZH) in Warsaw, an institution to which the Ministry of Public Health entrusted tasks related to health education in the country. The State School of Hygiene was built by the Polish Government with a significant financial contribution from the John Davison Rockefeller Foundation. The official opening ceremony took place on 20 April 1926. The State School of Hygiene in Warsaw was the first such school in Europe. It educated professional staff for the health service in Poland, especially sanitary physicians, sanitary inspectors, nurses and staff to work in health offices. The importance and scope of influence of the State School of Hygiene as the Department of Education in the National Institute of Hygiene was constantly increasing, as evidenced by the number of students (about 800 per year) participating in courses, especially in the first years after its establishment. By the end of 1935, 6,389 students had completed the courses, including 1,900 physicians. Apart from the teaching activities, the State School of Hygiene also carried out research work. The State School of Hygiene was supported by the Rockefeller Foundation, which funded scholarships for the employees of the National Institute of Hygiene at university centers in the USA.